Effects of repetitive transcranial magnetic stimulation on upper-limb and finger function in stroke patients: A systematic review and meta-analysis of randomized controlled trials - Chen, Gengbin; Lin, Tuo; Wu, Manfeng; Cai, Guiyuan; Ding, Qian; Xu, Jiayue; Li, Wanqi; Wu, Cheng; Chen, Hongying; Lan, Yue (Frontiers in Neurology, 2022)
Abstract Background: Repetitive transcranial magnetic stimulation (rTMS) is a promising intervention for stroke rehabilitation. Several studies have demonstrated the effectiveness of rTMS in restoring motor function. This meta-analysis aimed to summarize the current evidence of the effect of rTMS in improving upper limb function and fine motor recovery in stroke patients. Methods: Three online databases (Web of Science, PubMed, and Embase) were searched for relevant randomized controlled trials. A total of 45 studies (combined n=2064) were included. Random effects model was used for meta-analysis and effect size was reported as standardized mean difference (SMD). Results: rTMS was effective in improving fine motor function in stroke patients (SMD, 0.38; 95% CI 0.19–0.58; P=0). On subgroup analyses, for post-stroke functional improvement of the upper extremity, bilateral hemisphere stimulation was more effective than unilateral stimulation during the acute phase of stroke, and a regimen of 20 rTMS sessions produced greater improvement than <20 sessions. In the subacute phase of stroke, affected hemispheric stimulation with a 40-session rTMS regimen was superior to unaffected hemispheric stimulation or bilateral hemispheric stimulation with <40 sessions. Unaffected site stimulation with a 10-session rTMS regimen produced significant improvement in the chronic phase compared to affected side stimulation and bilateral stimulation with >10 rTMS sessions. For the rTMS stimulation method, both TBS and rTMS were found to be significantly more effective in the acute phase of stroke, but TBS was more effective than rTMS. However, rTMS was found to be more effective than TBS stimulation in patients in the subacute and chronic phases of stroke. rTMS significantly improved upper limb and fine function in the short term (0–1-month post-intervention) and medium term (2–5 months), but not for upper limb function in the long term (6 months+). The results should be interpreted with caution due to significant heterogeneity. Conclusions: This updated meta-analysis provides robust evidence of the efficacy of rTMS treatment in improving upper extremity and fine function during various phases of stroke. Keywords: repetitive transcranial magnetic stimulation, stroke, meta-analysis, Hand, Upper limb, review.